2013
DOI: 10.1364/ol.38.004104
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of Kramers–Kronig self-phasing in coherently combined fiber lasers

Abstract: A highly stable coherent beam-combining system has been designed to measure self-phasing in fiber lasers due to nonlinear effects. Whereas self-phasing in previous coherent combination experiments has been principally attributed to wavelength shifting, these wavelength effects have been efficiently suppressed in our experiment by using a dual-core fiber with closely balanced optical path lengths. The self-phasing from nonlinear effects could then be measured independently and directly by common-path interferom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The lasing wavelength of this coherently phased array was 1052 nm. The lasing power versus applied path length error data L. (blue squares) has the characteristics predicted by a cold-cavity theory 8 . Lasing power varies with the applied path length error nearly periodically with a period of π/2.…”
Section: Resultsmentioning
confidence: 76%
“…The lasing wavelength of this coherently phased array was 1052 nm. The lasing power versus applied path length error data L. (blue squares) has the characteristics predicted by a cold-cavity theory 8 . Lasing power varies with the applied path length error nearly periodically with a period of π/2.…”
Section: Resultsmentioning
confidence: 76%
“…Coherent beam combination (CBC) of fiber lasers is a promising technique to solve the power limitation but also maintain good beam quality. Many approaches of CBC have been demonstrated, which can be classified into two categories: active phase locking [3][4][5][6] and passive phase locking [7][8][9]. Active phasing have been demonstrated to have the advantage in combining a large number of beamlets, especially for fiber lasers [6].…”
Section: Introductionmentioning
confidence: 99%
“…However a complex system like a coupled array of lasers cannot be fully described without taking into account the intrinsic nonlinearity of the lasers. Thus, subsequent theoretical approaches including gain saturation and resonant phase nonlinearity [12][13][14][15] have shown that passive techniques to phase-lock a laser array could be more efficient than initially considered. In lasers based on a ytterbium doped fiber amplifier (YDFA) in particular, the resonant nonlinearity may be significant (especially on the long wavelength side 1070-1090 nm).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting gain-phase coupling leads theoretically to a linewidth enhancement factor close to one [12]. In a properly design cavity, the additional phase-shift accumulated during amplification may significantly impact the behavior and in-phase operation of the fiber laser network with scattered lengths [12][13][14][15]. In a recent paper, Chiang et al [15] experimentally demonstrated that the phase-shift due to population inversion in YDFA could actually compensate for the linear phase detuning between the two arms of a double channel fiber laser.…”
Section: Introductionmentioning
confidence: 99%